(untitled) (Bangladesh Journal of Nuclear Agriculture, 2025)
Fine and aromatic rice varieties, such as Kataribhog, hold significant commercial value in Bangladesh, particularly in regions like Dinajpur where Kataribhog is primarily cultivated. Despite its popularity, Kataribhog rice has a low yield (less than 2.50 t/ha) and is prone to lodging. To address these issues, a study was conducted using in vitro culture techniques combined with gamma irradiation (60Co) to improve the variety. Three different media (PT-100G, PT-011G, and PT-100) were used to induce callus, followed by exposure to varying radiation doses (10Gy, 12Gy, and 15Gy). The PT-100G medium found most effective, inducing an embryogenic callus formation rate of 32.93%, while PT-011G and PT-100 showed lower rates 27.87% and 11.11%, respectively. A radiation dose of 10Gy was found optimal, with an 80% survival rate for calli and the best plant regeneration outcomes. Bangladesh J. Nuclear Agric, 38(2): 151-159, 2024